Ritual in the "Pyramid Texts": syntax, text and meaning - Morales, Antonio J. ('Ilu. Revista de Ciencias de las Religiones, 2015)
This paper aims at the exploration of the ritual dimension in the Pyramid Texts, the earliest instance known to humankind of substantial religious literature. The variegated nature of the textual constituents in the corpus has prevented Egyptologists from understanding in depth the complexities of the collection and the original contexts in which these texts (rites) first emerged. The implementation of ritual theory to the corpus, particularly the syntax ritual approach, provides the scholars with an outstanding frame of analysis and interpretation of the corpus, its structure, and function. With the corpus anchored to the rules of ritual syntax, it is possible to expose its multiple layers of meaning for the deceased’s resurrection and salvation.
Keywords: Pyramid Texts; ritual; syntax; mortuary literature; recitations; groups; series; tradition; innovation; adaptation; Old Kingdom.